The Impact of Exploration Activities for Oil and Gas on the Lives of People in the Albertine Graben Region in Western Uganda. An Analysis of the Hoima District - Moses Arthur Kabonge (Uganda Christian University, 2025)
The study examined the impact of exploration activities for oil and gas on the lives of people in the Albertine graben region in western Uganda. an analysis of the Hoima District. With a growing focus on natural resource extraction in the region, understanding the implications of exploration activities on local communities' livelihoods is imperative for sustainable development. This was guided by the following objectives;- to find out the main exploration activities taking place and to establish the impact of oil and gas exploration activities on people’s livelihoods in Buseruka Sub-County, Hoima District. The Oil and Gas industry everywhere faces problems and challenges. However, in the developing countries, these difficulties and challenges are present alongside a general situation of socio-economic stress, chronic resource shortages, institutional weaknesses and a general inability to deal with the key issues. The study adopted an economic theory by Adam Smith (1776) the theory states that wealth is created via labor, and self-interest spurs people to use their resources to earn money. This was relevant since it is an influential figure of the Industrial Revolution in Uganda. Oil and gas exploration activities are an indication to the revolution of the sector. The Oil and Gas industry everywhere faces problems and challenges. However, in the developing countries, these difficulties and challenges are present alongside a general situation of socio-economic stress, chronic resource shortages, institutional weaknesses and a general inability to deal with the key issues. The researcher adopted a descriptive research design. This is done to identify and obtain information on the characteristics of a particular issue (Kothari, 2008). The sample involved 33 respondents and determined by Slovene’s formula. Findings indicate that the males were the most at 23(69.7%) with the females being the least at 10(30.3%). Results also indicates that government has conducted surveying of the land with mean 3.36 std.54 surveying is one of the oil and gas exploration activity taking place in Butiaba Sub country, 3.39 mean indicates that there is site clearance including the surrounding areas of communities in Butiaba sub county and it is what guided for the establishment of the oil and gas plant. The study also found out that livelihood sources were engaged in before and after commissioning of oil and gas exploration activities. Mean 3.48 indicated that people access to safe water for domestic use in the community. In summary, the exploration activities undertaken in Butiaba sub county have provided helpful insights into the region's geological composition and potential resource reserves. This entails strengthening oversight mechanisms to enforce compliance with environmental regulations and best practices, including rigorous environmental impact assessments (EIAs) throughout the exploration process
Undergraduate research